2020
DOI: 10.3390/ma13030648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiological Approach to Design and Optimize Bone Tissue Scaffolds 3D Printed with Fused Deposition Modeling: A Feasibility Study

Abstract: In spite of the rather large use of the fused deposition modeling (FDM) technique for the fabrication of scaffolds, no studies are reported in the literature that optimize the geometry of such scaffold types based on mechanobiological criteria. We implemented a mechanobiology-based optimization algorithm to determine the optimal distance between the strands in cylindrical scaffolds subjected to compression. The optimized scaffolds were then 3D printed with the FDM technique and successively measured. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…The experimental tests previously conducted with FDM demonstrated that this technique is suitable to build accurate scaffold samples only in the cases where the strand diameter is close to the nozzle diameter. Conversely, when a large difference exists, large fabrication errors can be committed on the diameter of the filaments [ 17 ]. Scaffolds fabricated with selective laser sintering (SLS) show dimensional deviations—with respect to the nominal dimensions—up to 7.5% [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental tests previously conducted with FDM demonstrated that this technique is suitable to build accurate scaffold samples only in the cases where the strand diameter is close to the nozzle diameter. Conversely, when a large difference exists, large fabrication errors can be committed on the diameter of the filaments [ 17 ]. Scaffolds fabricated with selective laser sintering (SLS) show dimensional deviations—with respect to the nominal dimensions—up to 7.5% [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The model includes also the granulation tissue, highlighted in red ( Figure 5 ), occupying the scaffold pores. Both the scaffold and the granulation tissue were modeled as biphasic poroelastic materials with the same material properties ( Table 1 ) as those utilized in previous studies [ 15 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The bed and nozzle temperature parameters are not inside the interval suggested by the 3D printer supplier, but since manufacturing time is lower than 5 min, the machine is able to complete the workpiece without damages. The different pore sizes were obtained setting on the Cura slicing software the distance between lines equal, respectively, to 0.75 mm for small pores, 0.9 mm for medium pores and 1.15 mm for large pores [ 29 ]. Figure 1 shows the Ultimaker 3D printer and samples of the manufactured scaffolds.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been reported that the FDM printing technique can accurately build scaffolds when the diameter of strands used to make PLA scaffolds were close to the nozzle diameter. On the contrary, in case of a large difference, fabrication errors were large and imposed on the filament diameter due to inappropriate material flow [272]. The strand diameters tested for nozzle diameter of 800 µm were 500, 600, 700, and 800 µm, and for nozzle diameter of 400 µm it was 400 µm.…”
Section: D Printing Process Optimizationmentioning
confidence: 99%